Study on Axial Stress Variation of Casing in Cementing Process - Xiang Wang (The International Journal of Multiphysics, 2024)
Cement slurry solidification process is an important part of cementing engineering, cement slurry solidification directly affects the quality of cementing, and then affects the whole drilling engineering and cost problems. In the process of cement slurry solidification, the decrease of slurry column pressure will increase the pull of upper casing, which is also the main reason for oil, gas, water channeling and early casing damage. In the process of cement slurry gelling, hydration will cause it to heat up, and then lose weight, and the combination of temperature and pressure will cause great deformation of the casing string. With the solidification of cement, this deformation will also be consolidated in the cement-sealed section. With the change of temperature and pressure under the injection-production condition, the casing in the sealed section may be under serious stress and strain, and may become an important factor affecting the service life of the casing. However, previous research on casing damage only focused on the completion of cementing. After cementing, due to the influence of formation high temperature and high pressure, construction and other factors in the later stage of oilfield production, people’s attention mainly focused on the mechanical and chemical effects, and rarely considered the change of casing state during the cement slurry gaging process. Therefore, it is necessary to study the stress and deformation rule of casing string during the weight loss of cement cement gel. This paper simulates the casing force and change under different working conditions under the influence of factors such as cement slurry density, cement ring length, admixtures and formation environment. It is found that the axial tension of casing increases step by step with the cement slurry setting time and tends to decline at last. The research of casing damage in the later period provides a reference.